Real World Fuel Consumption and Emissions From LDVs and HDVs - Weller, Konstantin; Lipp, Silke; Röck, Martin; Matzer, Claus; Bittermann, Andreas; Hausberger, Stefan (Frontiers in Mechanical Engineering, 2019)
Real world emissions and energy consumption behavior from vehicles is a key element for meeting air iquality and greenhouse gas (GHG) targets for any country. While CO2 fleet targets for vehicles are defined on basis of standardized test procedures, real driving conditions manifold parameters show large variabilities. Main differences are The main differences are: driving cycle, vehicle loading and driving resistances, ambient temperature levels, start conditions and trip length, gear shift behavior of the drivers, power demand from auxiliaries, and fuel quality. For the upcoming update of the Handbook Emission Factors for Road Transport (HBEFA 4.1) we have performed analysis, measurements and simulations to simulate real world energy consumption values for 2-wheelers, passenger cars (PC), light commercial vehicles (LCVs), and heavy duty vehicles (HDVs), creating so called emission factors (EF). EFs show fuel consumption or emission level in [g/km] and [#/km] for fuel, gaseous exhaust gas components and also for the particle number (PN). EFs are provided for a lot of different traffic situations covering stop & go up to highway for different road gradient categories. EFs are different for each vehicle category and for each powertrain technology and emission standard (from EURO 0 gasoline PC to EURO VI HDV with CNG engine). To produce the EFs, vehicle tests from chassis dyno and from on-board measurements were collected in 18 independent European labs to set up models for all vehicle segments in the passenger cars and heavy duty emission model (PHEM). The models for PC and LCVs were based on weight and road load data available from the type approval test, the worldwide harmonized light vehicles test procedure (WLTP), and then calibrated in a stepwise approach to consider all influences in real world driving. Finally, the results for new vehicle fleet fuel consumption values were compared with data from the fuel consumption monitoring data base. For HDVs, the models are based on data from the development of the HDV CO2 determination method (Regulation (EU) 2017/2400, “VECTO”). The main findings of the updates for HBEFA 4.1 are: Exhaust pollutant emission levels from passenger cars with EURO 6d-temp type approval are below the limit values also in real driving conditions. HDVs new vehicles real world emissions are low already since introduction of EURO VI in 2013. Deterioration effects, ambient temperature effects on NOx from diesel cars and cold start emissions are relevant influences for the fleet average emissions. Real world CO2 emissions are clearly higher than type approval emissions for cars and LCVs. Higher average loading, shares of vehicle mileages with roof boxes or trailers, wet road, winter tires etc. as well as real world usage of auxiliaries, such as HVAC systems are main reasons for these differences.